Interculturalidad en Salud: Reflexiones a partir de una Experiencia Indígena en la Amazonia Peruana - Cárdenas, Cynthia Giovanna; Pesantes, María Amalia; Rodríguez, Alfredo (Pontificia Universidad Católica del Perú. Fondo Editorial, 2017)
This article examines the main characteristics of the proposal on interculturality developed by an indigenous Amazonian organization of Peru for the training of indigenous youth as nurse technicians in intercultural health. It shows how the Interethnic Association for the Development of the Peruvian Jungle (Aidesep) appropriates the concept of interculturality, reconfigures and reconstructs it. Based on internal documents, institutional publications, testimonies of graduates of the intercultural health program, leaders and members of the technical team of the Indigenous Health Program of AIDESEP, we analyze the construction and implementation of the concept of interculturality. We also examin the way in which an indigenous organization becomes a proponent of interculturality, building an indigenous response for the training of health professionals prepared to provide culturally appropriate health services to the indigenous population. The proposal for the training of nurse technicians in intercultural health shows that it is possible for critical interculturality to move from discourse to practice when indigenous peoples develop their own intercultural proposals.

Este artículo presenta y analiza las principales características de la propuesta de interculturalidad desarrollada por una organización indígena amazónica del Perú en la formación de jóvenes indígenas como enfermeros técnicos en salud intercultural. A través de este programa de formación, mostramos cómo la Asociación Interétnica de Desarrollo de la Selva Peruana (Aidesep) se apropia del concepto de interculturalidad, lo resignifica y reconstruye en la práctica. A partir de documentos internos, publicaciones institucionales, testimonios de egresados, dirigentes y miembros del equipo técnico del Programa de Salud Indígena de Aidesep, analizamos la construcción e implementación del concepto de interculturalidad. Este artículo muestra la forma en que una organización indígena se vuelve un actor proponente de la interculturalidad, construyendo una respuesta indígena para la formación de profesionales técnicos, preparados para brindar atención en salud culturalmente apropiada a la población indígena. La propuesta de formación de enfermeros técnicos en salud intercultural demuestra que es posible que la interculturalidad crítica pase del discurso a la práctica cuando los pueblos indígenas construyen propuestas interculturales propias.
Interculturality in health: reflections from an indigenous experience in the Peruvian Amazon
Keywords: Interculturalidad; Pueblos indígenas; Salud intercultural; Amazonia; Perú; https://purl.org/pe-repo/ocde/ford#5.04.03